Kebudayaan Masyarakat Di Desa Sei Bamban Dan Kebudayaan Masyarakat Di Kota Perbaungan - Khumairani, Annisa; Syahputri, Wahyu Ningsih; Siregar, Rini Wahyuni (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
It is important to know the culture and society of rural and urban areas so that you can see the ties of friendship that the community has. Currently, the development that is carried out must be community-based or in other terms rural and urban areas include the presence of industry, but it is important to see how prepared the community is to accept the presence of industry. The most important thing is to change the work culture that exists in that place. The work culture of rural and urban communities experiences changes along with progress and success in entering the village. The economic system which initially depended on natural conditions and traditional technology will also experience changes with the presence of technological tools in culture. The impact of industry will also be the use of current technology in culture.